Case report and literature review: Conversion surgery for initially unresectable huge retroperitoneal liposarcoma after preoperative radiotherapy - Cheng, Sarah Hsin; Huang, Yen-Shuo; Lee, Hsin-Hua; Yen, Heng-Hsuan; Jhong, Ying-Pei; Chao, Tzu-Yuan (Frontiers in Oncology, 2023)
Background Retroperitoneal liposarcoma (RPLS) is a rare malignancy that is notorious for recurrence. Surgical resection with clean margin is the current treatment of choice. However, owing to the large retroperitoneal space, RPLSs often grow to significant sizes before being diagnosed. Neoadjuvant and adjuvant therapies have potentials to improve long term treatment outcome. Case presentation A 55-year-old Han Chinese male presented to the general surgery department with a one-year history of abdominal fullness and a one-week history of palpable right inguinal mass. At first, he was diagnosed with incarcerated inguinal hernia. However, abdominal computer tomography (CT) and biopsy confirmed his final diagnosis to be retroperitoneal well-differentiated liposarcoma, cT2bN0M0, stage IIb. The tumor, which measured 44.5cm in maximum diameter, was too large for primary surgical resection. Neoadjuvant radiotherapy with 70 Gy in 35 fractions was delivered to the tumor, which shrunk the target volume from 6300 cc to 4800 cc, as observed in the middle of the radiotherapy course. The right testicular mass also received 70Gy/35Fx. Conversion surgery was performed after radiotherapy. Unfortunately, due to residual tumor, adjuvant chemotherapy consisting of AIM (ifosfamide, Mesna, and doxorubicin) and MAID (Mesna, doxorubincin, ifosfamide, and dacarbazine) regimens were administered sequentially. Afterward, debulking surgery was conducted, plus another 18 cycles of ifosfamide monotherapy when residual tumor was still seen on CT. Since the completion of ifosfamide chemotherapy, the patient has been cancer free with no evidence of tumor recurrence for more than 26 months. Conclusion Despite conflicting evidence in the literature, our case supports the use of high dose neoadjuvant radiotherapy and adjuvant chemotherapy in treating large, unresectable RPLSs. It also highlights the importance of using individualized, multidisciplinary approach in achieving cure for large, unresectable rare tumors.